2002
DOI: 10.1017/s0952523802192029
|View full text |Cite
|
Sign up to set email alerts
|

NMDA-evoked [Ca2+]i increase in salamander retinal ganglion cells: Modulation by PKA and adrenergic receptors

Abstract: Application of NMDA induces a depolarization and increase of intracellular calcium concentration ([Ca2+]i) in retinal ganglion cells, which cause ganglion cell death in models of glaucoma. In the present study, we investigated the pharmacological mechanism of how NMDA-evoked increase in calcium could be modulated in dissociated retinal ganglion cells from tiger salamander. In these neurons, protein kinase A (PKA) up-regulated the NMDA-evoked [Ca2+]i increase. In the presence of 8-bromo-cAMP or forskolin to sti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…Of interest, brimonidine protects RGCs by preventing the increase in intracellular calcium concentration ([Ca 2+ ] i ) induced by activation of NMDARs (92, 94, 105). Furthermore, brimonidine reduces NMDA-evoked [Ca 2+ ] i increase, while isoproterenol, a β adrenergic receptor agonist, enhances NMDA-evoked [Ca 2+ ] i increase via a cAMP/PKA signaling pathway dependent manner (107). These results strongly suggest that brimonidine-mediated inhibition of the cAMP/PKA pathway could be an important mechanism to protect RGCs against glutamate excitotoxicity-induced glaucomatous neurodegeneration.…”
Section: Camp In Rgcsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of interest, brimonidine protects RGCs by preventing the increase in intracellular calcium concentration ([Ca 2+ ] i ) induced by activation of NMDARs (92, 94, 105). Furthermore, brimonidine reduces NMDA-evoked [Ca 2+ ] i increase, while isoproterenol, a β adrenergic receptor agonist, enhances NMDA-evoked [Ca 2+ ] i increase via a cAMP/PKA signaling pathway dependent manner (107). These results strongly suggest that brimonidine-mediated inhibition of the cAMP/PKA pathway could be an important mechanism to protect RGCs against glutamate excitotoxicity-induced glaucomatous neurodegeneration.…”
Section: Camp In Rgcsmentioning
confidence: 99%
“…Our previous report demonstrated that functional NMDARs are present in human ONH astrocytes, and its expression levels are increased in cultured ONH astrocytes from patients with glaucoma (122). Because brimonidine-mediated tmACs inhibition protects RGCs against NMDARs-mediated glutamate excitotoxicity (107), these findings suggest another possibility, that brimonidine may also protect astrocytes by inhibiting tmACs activation in glaucomatous ONH degeneration. Although future studies need to investigate the effect of brimonidine on ONH astrocytes, this idea is supported by the evidence that the activation of metabotropic glutamate receptors 3, a GPCR linked to G αi subunit, protects cultured astrocytes against hypoxic/ischemic damage by tmACs inhibition (150, 151).…”
Section: Camp In Onh Astrocytesmentioning
confidence: 99%
“…Although the mechanisms for these protections are not completely understood, available data show that brimonidine can decrease adenyl cyclase (Dong et al, 2008), inhibit voltage-gated Ca 2+ channels (Han and Wu, 2002), activate receptor-operated K + channels (DeBock et al, 2003), and up-regulate anti-apoptotic genes such as bcl-2, bcl-xl, and several growth factors (Lai et al, 2002;Lo¨nngren et al, 2006). Most importantly, brimonidine can alleviate glutamate-induced neurotoxicity and prevent an ischemia-induced rise in extracellular glutamate (Donello et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to these molecular mechanisms, the neuroprotective effects of brimonidine are also due to a reduction in NMDA-elicited intracellular signals [Dong et al, 2008;Han and Wu, 2002]. Notably, NMDA receptors in the cochlea may be involved in the ototoxic effects of aminoglycosides, and NMDA receptor antagonists attenuate these ototoxic effects [Basile et al, 1996;Nagy et al, 2004].…”
Section: Brimonidine Does Not Significantly Change the Activation Levmentioning
confidence: 99%
“…In addition to these molecular mechanisms, brimonidine has also been shown to have neuroprotective properties via N-methyl-D -aspartate (NMDA) inhibition [Dong et al, 2008;Han and Wu, 2002], growth factor upregulation [Gao et al, 2002;Kim et al, 2007;Lonngren et al, 2006], and involvement in apoptotic pathways [Cai et al, 2013a;Lai et al, 2002]. Furthermore, brimonidine inhibits protein kinase A [Grueb et al, 2008].…”
mentioning
confidence: 99%